9-Deazaguanine and its methyl derivatives : synthesis, antitumor activity in vitro and effects on purine nukleoside phosphorylase gene expression - Suver, Mirjana (Array, 2008)
Summary: 9-Deazaguanine 9-DG, 1-methyl-9-deazaguanine AG-19-K1 and 1,7-dimethyl-9-deazaguanine AG-3 were synthesized and their antiproliferative activity against five leukemia and four solid tumor cell lines as well as inhibitory properties vs. calf spleen purine nucleoside phosphorylase (PNP) were tested. Synthesis of 9-DG involves reaction of 2-amino-6-methyl-5-nitropyrimidin- 4(3H)-one (2) with DMF-dimethylacetal (amount ratio, n(2) / n(DMF-dimethylacetal) = 1:2.5) and use of the benzyloxymethyl group to protect the N-3 position of 2-(N-dimethylaminomethylene) amino-6-methyl-5-nitropyrimidin-4(3H)-one (4). Reaction of 2 with DMF-dimethylacetal (amount ratio, n(2) / n(DMF-dimethylacetal) = 1:6) gave the N-3 methyl substituted intermediate 3. Dithionite reduction of this product afforded N-methyl derivatives AG-19-K1 and AG-3. AG-19-K1 and AG-3 were inactive vs. calf spleen PNP at a concentration of 75 mmol dm–3. Cytotoxic effects of 9-deazaguanine derivatives on cell growth were determined by the MTT assay. Investigated derivatives showed moderate antiproliferative activity towards examined tumor cells. At a concentration of 10–3 mol dm–3, AG-19-K1 inhibited the growth of JURKAT, K562 and AGS cells by approximately 80 %. At the same concentration, AG-3 and 9-DG inhibited cell proliferation by 40-50 % of all tested lines, except MOLT-4 and HL-60. The PNP gene expression was changed in treated leukemia cells after exposure to AG-19-K1 and 9-DG in a time-dependent manner